An editorial in four parts. Issue 3 (3rd May 2016) - Daniels, Kevin
Abstract : In writing this editorial, I have four objectives: (1) to make statement concerning EJWOP's mission—in particular, why does the world need a European Journal of Work and Organizational Psychology; (2) to review the state of our scientific practice and how EJWOP can help contribute to that practice; (3) to make a statement on the kind of papers EJWOP will strive to publish; and (4) to say thanks to the out-going editor and associate editors.